2021
DOI: 10.1016/j.poly.2021.115261
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted synthesis of anhydrous lanthanide-based coordination polymers built upon benzene-1,2,4,5-tetracarboxylic acid

Abstract: A series of trivalent lanthanide and group 3 metal coordination polymers with pyromellitic acid [M(Hbtec)]n (M = Eu, Dy, Sm, Nd, Ce, Er, Y) has been synthesized and structurally characterized. Contrary to most of coordination polymers, the reported compounds do not present any crystallized solvent molecules, and consequently they are thermally stable until 400-500°C. Moreover, they also exhibit good stability in water on a wide pH range. Compounds were synthesized by hydrothermal route with conventional heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…From a crystal engineering point of view, it is possible to modify the structural features using different synthetic methodologies, reaction conditions and use of ancillary ligands [60]. Within the most used synthetic techniques are (i) hydro or solvothermal synthesis, (ii) slow solvent evaporation, (iii) gel diffusion, (iv) mechanochemical, and (v) microwave-assisted synthesis [61][62][63][64][65][66][67]. It has been observed that the use of methodologies that involve the application of energy favors the formation of structures that are more compact, with more complex coordination modes and high dimensionalities [68].…”
Section: Flexible Linkers With -Ch 2 -Spacersmentioning
confidence: 99%
“…From a crystal engineering point of view, it is possible to modify the structural features using different synthetic methodologies, reaction conditions and use of ancillary ligands [60]. Within the most used synthetic techniques are (i) hydro or solvothermal synthesis, (ii) slow solvent evaporation, (iii) gel diffusion, (iv) mechanochemical, and (v) microwave-assisted synthesis [61][62][63][64][65][66][67]. It has been observed that the use of methodologies that involve the application of energy favors the formation of structures that are more compact, with more complex coordination modes and high dimensionalities [68].…”
Section: Flexible Linkers With -Ch 2 -Spacersmentioning
confidence: 99%
“…LnMOFs (MOFs based on trivalent lanthanides) containing dicarboxylate linkers show an intriguing variety of crystal structures and topologies due to their usually high coordination number leading to cluster units and polymeric chains most frequently observed for these compounds. In particular LnMOFs, in which both Ln 3+ and linkers can be used to give rise to luminescence materials (through antenna effect) with increased brightness and emission quantum yield, are a very promising class of materials in a wide range of optical applications including lasers, imaging agents, lighting systems, display applications, and ions recognition [ 16 , 17 , 18 , 19 , 20 ]. Especially, polynuclear hydroxidolanthanide based cluster metal-organic frameworks are important type of LnMOFs and attracting increasing attentions in view of their optical, electronic and catalytic properties, which may primarily lead to potential various applications such as optoelectronic devices, biocatalyst and luminescent materials [ 21 ].…”
Section: Introductionmentioning
confidence: 99%